The Market for Corporate Control and Firm Innovation - Hitt, Michael A.; Hoskisson, Robert E.; Johnson, Richard A.; Moesel, Douglas D. (Academy of Management Journal, 1996)
This research examines an integrated theoretical model that explains how strategies for participating in the market for corporate control (acquisitions and divestitures) affect internal control mechanisms and, together, influence internal and external innovation. Nine out of ten hypotheses received support, with results showing that firms engaging in acquisitions and divestitures emphasize financial controls, deemphasize strategic controls, and thereby produce less internal innovation. Furthermore, these firms are likely to seek external innovation to gain short-term benefits in competitive advantage. We conclude that engaging in the market for corporate control strongly affects the context in which innovation is framed, the control mechanisms employed, and the design and process of innovation.